IMPLEMENTASI UU NO. 23 TAHUN 2011 TENTANG PENGELOLAAN ZAKAT PADA BAZNAS KOTA PAREPARE - Aidil Aditya; Zainal Said; Rukiah (Indonesia Journal Of Zakat And Waqf, 2022)
Zakat is one of the obligations of Muslims that has been stipulated in the Qur'an and explained in detail in the hadith of the Prophet Muhammad in its application, and also in the consensus of the scholars. BAZNAS (Badan Amil Zakat Nasional) of Parepare City is a non-structural institution in the local government in the field of managing, collecting, and utilizing zakat, infaq, and alms in Parepare City, which consists of government and community elements. This research is qualitative research with field research methods. This research was conducted by looking for data sourced from BAZNAS Parepare City, especially on the part of implementing zakat management and looking at the implementation of Law No. 23 of 2011, especially in Article 22 concerning Zakat issued by muzakki will be deducted from taxable results. The results of this study indicate that the management of zakat in Parepare City has been managed by BAZNAS of Parepare City since 2017 and its management is in accordance with the rules applied according to sharia and government regulations. However, local government employees in Parepare City are still around 20% who issue zakat. Law Number 23 of 2011 concerning the management of zakat related to zakat payments made by muzakki whose application is that zakat paid is deducted from taxable income has not been maximally implemented in the local government of the city of Parepare, this is because employees do not implement these rules and what is known is that only obligation to pay zakat.